Suppressing thoughts of evaluation while being evaluated. Issue 1 (19th December 2013) - Slepian, Michael L.; Oikawa, Masanori; Smyth, Joshua M.
Abstract Thought suppression can cause ironic increases in the occurrence of intrusive thoughts. Intrusive thoughts of evaluation could be especially disruptive while undergoing evaluation. Such a context, however, could help suppression efforts as the context provides an external source for which to attribute suppression failures. When suppressing thoughts of evaluation in a non‐evaluative context (a context‐content mismatch), typical ironic effects of thought suppression occurred. There was no increased accessibility of evaluation, however, when suppressing evaluation in an evaluative context (a context‐content match), which allowed for attributing intrusive thoughts to the context, rather than the self, making suppression easier. Suppressing thoughts of evaluation may be beneficial in an evaluative context, suggesting that the consequences of willful suppression are moderated by context.